Optimal PID Controller Designing for Uncertain Bioreactor Using BFO Algorithm (International Journal of Engineering and Computer Science, 2016)
— Bioreactor plays major role in chemical, biochemical and pharmaceutical industries. The final product quality in a bioreactor depends mainly on the control system employed to supervise and regulate the process. In this article, modified Bacterial Foraging Optimization (BFO) algorithm supported PID controller design is attempted for the bioreactor operating at unstable steady state region. Weighted sum of multiple objective functions is considered as the cost function, which directs the BFO algorithm to find the optimal controller parameters. In this work, an uncertainty of ± 10% is assigned in the process model constraints such as process gain (K), time constant (τ) and delay time (θ). The BFO algorithm based search finds the minimal and maximal values of controller parameters such as Kp, Ki and Kd. The competence of the proposed method has been confirmed through a simulation work. The results show that, the proposed method provides smooth performance in effective reference tracking with minimal error values.